ANALISIS MODEL PEMBELAJAN PROBLEM BASED LEARNING DALAM MATA PELAJARAN MEKANIKA TEKNIK PADA PENDIDIKAN VOKASIONAL - Ravino Indra Julio; Riyan Arthur (ADISAM PUBLISHER, 2025)
This study evaluates the effectiveness of Problem-Based Learning (PBL) in the context of education, particularly in Mechanical Engineering subjects. Its aim is to enhance students’ understanding of Mechanical Engineering concepts and identify its positive impact on learning outcomes. The method employed is literature review, involving data collection and analysis from various literature sources. The study demonstrates that PBL significantly benefits students’ learning outcomes across different educational contexts. Several studies support the notion that PBL improves students’ critical thinking, problem-solving skills, and collaborative abilities in understanding Mechanical Engineering concepts. These findings provide a robust foundation for the development and implementation of PBL in education, including vocational high schools and Mechanical Engineering subjects. The conclusion drawn is that PBL is an effective learning approach, especially in the context of Mechanical Engineering education, by engaging students in solving real-life problems. Therefore, the adoption of PBL is expected to enhance overall educational quality and better prepare students for the increasingly complex demands of the future workforce. Suggestions for further research include continuously developing and testing innovative teaching methods, including PBL, and enhancing collaboration and supportive educational policies. Regular evaluation of teaching method effectiveness is also crucial to ensure learning objectives are achieved. It is anticipated that this research will make a significant contribution to the advancement of education in the future